The extracellular vesicles targeting tumor microenvironment: a promising therapeutic strategy for melanoma - Li, Yongmin; Liu, Fei (Frontiers in Immunology, 2023)
Extracellular vesicles (EVs) are small particles secreted by numerous cell types and circulate in almost all body fluids, acting as crucial messengers for cell-to-cell communication. EVs involves multiple physiological and pathological processes, including tumor progression, via their multiple cargoes. Therefore, EVs have become attractive candidates for the treatment of tumor, including melanoma. Notably, due to the crucial role of the tumor microenvironment (TME) in promoting tumor malignant phenotype, and the close intercellular communication in TME, EVs-based therapy by targeting TME has become a cutting-edge and prospective strategy for inhibiting melanoma progression and strengthening the anti-tumor immunity. In this review, we aimed to summarize and discuss the role of therapeutic EVs, which target the components of TME in melanoma, thereby providing insights into these promising clinical strategies for the treatment of melanoma patients.